FASHION STYLE SPG DALAM MEMASARKAN PRODUK DITINJAU DARI PERSPEKTIF AL-QUR’AN - Santi Marito (Institut agama islam negeri Padangsidimpuan, 2020)
Sales promotion girl (SPG) is a profession in the field of product promotion or marketing. Usually this profession uses the services of women who look attractive and look sexy in clothes to attract consumers. In addition to attracting consumers, this is done to increase company sales. This study uses qualitative methods and uses analytical descriptors as data analysis, the source of the data in this study is sourced from the Qur'an, commentaries, books, articles and journals. The results of this study conclude several conclusions, namely: first, SPG fashion style in marketing products is demanded to look attractive. SPG cigarettes and Hyundai carry the sexy and glamorous SPG concept, SPG wears a mini top and miniskirt, complete with high heels as well as thick makeup. SPG oppo and vivo smartphones wear uniform shirts and jeans. Whereas SPG cosmetics Wardah wears loose tops, trousers and also a veil that covers her. Second, the term clothing in the Qur'an is expressed in nine terms, namely: libas, tsiyab, sarabil, zinah, khimar, jalabib, qamish, risy, and kiswah. These nine terms consist of two categories, namely clothing in the intrinsic sense and clothing with the meaning of majazi. Third, the guidance of the qur’an in general dress is that the clothes to be worn are wide, loose, not transparent, cover the entire genitals, do not resemble men's clothing and do not resemble the clothes of the infidels.